2006
DOI: 10.1021/om051064r
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Complexes Containing 17-Ethynyl-17β-hydroxyandrost-4-en-3-one and Related Ethynyl Steroids

Abstract: Gold complexes of 17-ethynyl-17β-hydroxyandrost-4-en-3-one, 17-ethynyl-3-methoxyestra-1,3,5(10)-trien-17β-ol, and 17α-ethynylestra-1,3,5(10)-triene-3,17β-diol have been prepared and characterized. The title compounds were prepared by treatment of the parent ethynyl steroid with sodium bis(trimethylsilyl)amide followed by the addition of R3PAuCl. Using a variety of phosphorus donors, a total of 36 gold steroid compounds were readily prepared using this approach. Compounds containing basic low cone angle phosphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Reductive elimination would afford the observed products. Our own attempts to effect an oxidative addition reaction between aryl halides and gold substituted ethynylsteroids 78 were unsuccessful and only starting materials were recovered. These observations were supported by a recent report which outlined problematic oxidative addition reactions of aryl halides to gold(I) centers.…”
Section: P-h Activation Studiesmentioning
confidence: 99%
“…Reductive elimination would afford the observed products. Our own attempts to effect an oxidative addition reaction between aryl halides and gold substituted ethynylsteroids 78 were unsuccessful and only starting materials were recovered. These observations were supported by a recent report which outlined problematic oxidative addition reactions of aryl halides to gold(I) centers.…”
Section: P-h Activation Studiesmentioning
confidence: 99%
“…Recently we have witnessed a revival of gold complexes in medicinal chemistry and new results have demonstrated that gold complexes are promising anticancer [15,16,17,18] and antimicrobial [19,20] drug candidates. The majority of biologically tested gold complexes focus on gold ions in the +1 oxidation state and generally bound to thiolates [21,22], to various N -heterocyclic carbenes (NHC) [23,24,25,26,27], to diphos-type [28] and alkyne [29,30,31,32,33,34,35] ligands. There is also an increased interest in the development of anticancer gold(III)-NHC complexes [36,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…These alterations ultimately lead to the pro-apoptic proteins signalling induction [27,40,42]. In comparison to the other classes of biologically investigated gold(I) complexes [15,18,19,20,23,24,25,26,27,40,41] gold(I)-alkynyl complexes have been studied to the very limited extent [29,30,31,32,33,34,35]. Moreover, to the best of our knowledge to date there has not been any reported data on the antibacterial activity of gold(I)-alkynyl complexes although some in vitro antimalarial activity in two strains of Plasmodium falciparum has been published [32].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Of the gold(I) complexes reported to have anti-cancer activity, alkynyl-gold(I)-phosphine complexes are among the most potent. [5][6][7][8][9][10][11][12][13][14] The incorporation of a second different metal centre into a complex can alter the physiochemical properties significantly. This can be advantageous in the development of chemothera- For ESI and crystallographic data in CIF or other electronic format see DOI: 10.1039/d0dt02113j peutic agents as a means of enhancing cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%